Characterization of the c-MYC-regulated transcriptome by SAGE: Identification and analysis of c-MYC target genes - Menssen, Antje (The National Academy of Sciences, 2002)
To identify target genes of the oncogenic transcription factor c-MYC, serial analysis of gene expression (SAGE) was performed after adenoviral expression of c-MYC in primary human umbilical vein endothelial cells: 216 different SAGE tags, corresponding to unique mRNAs, were induced, whereas 260 tags were repressed after c-MYC expression (P < 0.05). The induction of 53 genes was confirmed by using microarray analysis and quantitative real-time PCR: among these genes was MetAP2/p67, which encodes an activator of translational initiation and represents a validated target for inhibition of neovascularization. Furthermore, c-MYC induced the cell cycle regulatory genes CDC2-L1, Cyclin E binding protein 1, and Cyclin B1. The DNA repair genes BRCA1, MSH2, and APEX were induced by c-MYC, suggesting that c-MYC couples DNA replication to processes preserving the integrity of the genome. MNT, a MAX-binding antagonist of c-MYC function, was up-regulated, implying a negative feedback loop. In vivo promoter occupancy by c-MYC was detected by chromatin immunoprecipitation for CDK4, Prohibitin, MNT, Cyclin B1, and Cyclin E binding protein 1, showing that these genes are direct c-MYC targets. The c-MYC-regulated genes/tags identified here will help to define the set of bona fide c-MYC targets and may have potential therapeutic value for inhibition of cancer cell proliferation, tumor-vascularization, and restenosis.